Darnios pastatų architektūros genotipas ir fenotipas - Kamičaitytė-Virbašienė, Jūratė; Gražulevičiūtė-Vileniškė, Indrė (Journal of Architecture and Urbanism, 2011)
Phenotype and genotype of sustainable building architecture Sustainable design and construction are the trends of environmental design and management gaining an increasing acknowledgement and popularity. The definitions targeted at the environmentally friendly building architecture, such as “sustainable architecture”, “ecological architecture”, “green architecture” are widespread in literature; however, the analysis of literature has also revealed the insufficient attention to the theoretical basis of the application of the principles of sustainability to the field of architectural design: no unified definition of sustainable building architecture is provided, insufficient attention is devoted to the visual and aesthetic aspects of sustainable design, to the links of sustainable buildings with the contextual environment, and the wider influence of the sustainable architectural design on the development of the built environment is also rarely analysed. These aspects of the problem justify the aim of the article, which is to highlight the main features of sustainable building architecture, the main trends of its visual expression, and to link them with the particular contextual environments using the example of Kaunas city. The entire analysis is carried out using analogies from natural sciences – genotype and phenotype – and the character of their interconnections. Article in Lithuanian. Santrauka. Darnus projektavimas ir darni statyba – tai vis labiau populiarėjančios ir plačiau pripažįstamos aplinkos formavimo veiklos kryptys. Nors literatūroje dažnai sutinkami aplinką tausojančią pastatų architektūrą apibūdinantys terminai, tokie kaip „darni architektūra“, „ekologiška architektūra“, „žalioji architektūra“, tačiau kartu pastebimas ir nepakankamas dėmesys teoriniam darnaus vystymosi principais paremto projektavimo pagrindui: nėra pateikiamas konkretus darnios pastatų architektūros apibrėžimas, mažai skiriama dėmesio vizualiniams, estetiniams darnaus projektavimo klausimams, darnios architektūros pastatų santykiui su kontekstine aplinka, darnaus vystymosi principais paremtos architektūros kūrimo įtakai darniam užstatytos aplinkos vystymuisi platesniu mastu. Šie problemos aspektai pagrindžia straipsnio tikslą – remiantis iš gamtos mokslų perimtomis genotipo ir fenotipo sąvokomis ir jų tarpusavio sąsajomis, išryškinti svarbiausius darnios pastatų architektūros bruožus, jos vizualinės raiškos kryptis ir, remiantis Kauno miesto pavyzdžiu, susieti jas su konkrečia kontekstine aplinka. Reikšminiai žodžiai: darnus vystymasis, darni architektūra, genotipas, fenotipas, Kaunas. First Publish Online: 22 May 2013